Teachers’ Attitude on Reflective Practice-Based Instruction in Teaching English in Indonesian EFL Classroom - Citra Prasiska Puspita Tohamba; Kisman Salija; Muhammad Basri (Sintuwu Maroso Journal of English Teaching, 2022)
This paper reports a study of teacher’s attitude on reflective practice-based instruction in teaching English in Indonesian EFL classroom. Teachers are urged to feel reactive and open minded as the prerequisite for being reflective teachers. It is also crucial to EFL teachers due to they are required to teach students about course content and language development. Thus, reflective teaching-based instruction comes as a catalyst of teachers’ professional performance in teaching English as a Foreign Language (TEFL). The study employs a descriptive qualitative study utilizing questionnaire and in-depth interview, taking three teachers as the participant of the study selected through conveniently sampling technique. Then, thematic analysis was used to analyse the findings of data. The result of the study demonstrates that there were marked differences in the way the teachers perceive reflective practice based instruction in their classroom teaching practices. The differences fall into three categories: (1) highly adjusted of reflective practice (HARP), (2) moderately adjusted of reflective practice (MARP), and (3) poorly adjusted of reflective practice (PARP).This study can be beneficial input to enhance understanding and practice of the use of reflective practice-based instruction in EFL classroom, especially in Indonesian context.